Nature connectedness and biophilic design. Issue 1 (17th February 2022) - Richardson, Miles; Butler, Carly W.
ABSTRACT: Biophilic design involves the creation of built environments that promote connection between humans and nature. While literature reviews show support for the psychological and health benefits of biophilic design, they note that the evidence base is heavily focused on the restorative efficacy of various natural elements (e.g. light, water and wood) and experiences (direct, indirect, space and place). There has been little consideration of Kellert and Calabrese's [(2015). The practice of biophilic design . Terrapin Bright LLC.] key principles of biophilic design and the holistic approach to design that has nature connection at its heart. This perspective article discusses the biophilic design principles in light of research on the psychological construct of nature connectedness. The research offers empirical support for the importance of key biophilic design principles – the need for repeated and sustained engagement with nature, for encouraging an emotional attachment to settings and places and for promoting interactions between people and nature that foster a greater sense of relationship and responsibility for human and natural communities. An evidence-based framework for the application of biophilic principles and experiences into the design process is proposed. Recommendations for optimizing the application and evaluation of biophilic design principles and practices are made, in order to support the well-being of humans and nature.